Pola Struktur Gaya Bahasa Tasybīh dalam Al-Qur'an - Ilham, Muhammad Arifin; Hibatullah, Fairuz Azhar; Sopian, Asep; Nurmala, Mia (Study Program of Arabic Language Teaching, 2024)
This research aims to determine the structural analysis of the tasybih language style in the verses of the Al-Qur'an. With a literature study approach, the qualitative method collects data by understanding and studying theories from various relevant literature sources. The main data source in this research is the Al-Qur'an, while additional data sources were obtained from various journals and research articles about Tasybih. Next, data from these research sources will be classified to find several Qur'an verses containing Tasybih. After the data from the research source is presented, the final step is to verify or conclude from the data that has been collected. At this stage, analysis is carried out to identify Koran verses containing Tasybih. The research results show that although Bayan Science has several discussion branches, Tasybih has its function and characteristics. There are similarities in the structure of the 7 Tasybih verses in the Al-Qur'an studied: they are all in the form of mujmal tasybih. It is hoped that this research can provide a deeper understanding of Tasybih and contribute to the study of Arabic linguistics and literature in general.